Alternative Construction Jurisprudence of Plain Language: A Deliberation on the Synchronisation of the Nigerian Legal Framework - Etudaiye, Muhtar (NIU Journal of Humanities, 2017)
One of the greatest problems for obedience to laws is the comprehension of laws by ordinary citizens. As a consequence of this, laws are generally obeyed by default in an unconscious manner. This is more so in a country such as Nigeria where literacy is very low and the standard of education has been acknowledged to have fallen in standard over the years. This article emphasizes the need for a tilt towards plain language lawmaking as an alternative jurisprudence for the legal draftsman. It addresses the challenges that the draftsman has to surmount and arrives at the conclusion that legalese is not necessarily more compact with respect to wastage of words than plain language. In view of the findings, the article, using doctrinal and analytical methods, made some recommendations with a view to addressing and improving comprehension of legal texts by ordinary people. Keywords: Deliberation, Synchronisation, Nigeria, Legal, Framework, Alternative, Construction, Jurisprudence, Plain, Language.